Design, Synthesis, and Biological Evaluation of the Sex Pheromone of the Asian Corn Borer, Ostrinia furnacalis (Guenée) - Zhengchang Lu; Wei Liu; Hongyu Pan; Dawei Zhang (Journal of Chemistry)
A convenient total synthesis of (Z)-12-tetradecenyl acetate (1a) and (E)-12-tetradecenyl acetate (1b), which are the sex pheromones of Ostrinia furnacalis (Guenée), has been achieved. The target mixture molecules, of a cis-to-trans-isomer ratio of 27 to 73, were synthesized in 40% overall yield and through [13C + 1C] synthetic strategy in five steps from commercially available and cheap industrial brassylic acid as key starting material. The electroantennogram (EAG) responses of synthetic sex pheromone to ACB male moths were conducted. The results showed that the target mixture molecules were found to have a good activity and displayed significantly stronger EAG responses ranging from 10 to 1000 μg, and the optimized stimulating dosage of the activity of synthetic sex pheromone to ACB males is 10 μg. Compared with the existing routes, this synthetic approach is operationally simple, good-yielding, and cost-effective, which could serve as a basis for developing the techniques of sex pheromone mass trapping or mating disruption and providing an environmentally benign method to control ACB pests.